2023
DOI: 10.3389/fmed.2023.1198720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of individualized positive end-expiratory pressure based on electrical impedance tomography guidance on pulmonary ventilation distribution in patients who receive abdominal thermal perfusion chemotherapy

Li Xiao,
Kang Yu,
Jiao-Jiao Yang
et al.

Abstract: BackgroundElectrical impedance tomography (EIT) has been shown to be useful in guiding individual positive end-expiratory pressure titration for patients with mechanical ventilation. However, the appropriate positive end-expiratory pressure (PEEP) level and whether the individualized PEEP needs to be adjusted during long-term surgery (>6 h) were unknown. Meanwhile, the effect of individualized PEEP on the distribution of pulmonary ventilation in patients who receive abdominal thermoperfusion chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The second reason is that all patients in our study had heart disease, leading to an imbalance in oxygen supply and demand in the myocardium. The use of PEEP can be detrimental to circulatory stability, and hemodynamic fluctuations may lead to inadequate blood and oxygen supply to the lung tissues, thereby increasing the chance of pulmonary complications ( 35 ). Although some previous studies have shown that PEEP did not reduce PPCs, the lack of corresponding previous studies on lung protection during one-lung ventilation in the prone position resulting from HCR prevents us from validating our findings ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second reason is that all patients in our study had heart disease, leading to an imbalance in oxygen supply and demand in the myocardium. The use of PEEP can be detrimental to circulatory stability, and hemodynamic fluctuations may lead to inadequate blood and oxygen supply to the lung tissues, thereby increasing the chance of pulmonary complications ( 35 ). Although some previous studies have shown that PEEP did not reduce PPCs, the lack of corresponding previous studies on lung protection during one-lung ventilation in the prone position resulting from HCR prevents us from validating our findings ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%